A Systematic Literature Review on Impact of Industrial Revolution 4.0 in Indonesia's Agriculture Sector - Kiki Pranowo; Ida Widianingsih; H. Heru Nurasa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Technology always plays a significant role for humans in simplifying and optimizing tools and ideas to solve problems. When the first society was created began with foraging and livestock, the population increased. The Industrial Revolution 4.0 significantly impacted agriculture at the country level in a tolerable and understandable way. This paper aims to assess the implementation of preparation IR. 4.0 in Indonesia achieved its objectives or could be optimized. The previous research was in general and mainly focused on technological factors. . Indonesia is the fourth most populous country globally, and many of its citizens depend on their livelihood from the agriculture sector (Badan Pusat Statistik / Central Bureau of Statistic, 2021). Based on the national policy of Making Indonesia 4.0 and programs implemented in The Ministry of Agriculture, This research employs both quantitative and qualitative methods. A systematic review was conducted to check published articles regarding the topic from Food and Agricultural Organization (FAO) and Indonesian Governmental Institutions. To fully understand the topic, four research sources were used to find relevant data published between 2000 and 2021. The inclusion criteria were related to the IR 4.0 impact on the agriculture sector, original research, and published in English. Thirty articles have met the criteria. The findings have shown that IR 4.0 has revolutionized agriculture to become Agriculture 4.0, and various innovations are taken to increase the productivity of food production. Applications also built a stepping stone but yet worked for one purpose only.